Financial Stress Interacts With CLOCK Gene to Affect Migraine - Baksa, Daniel; Gonda, Xenia; Eszlari, Nora; Petschner, Peter; Acs, Veronika; Kalmar, Lajos; Deakin, J. F. William; Bagdy, Gyorgy; Juhasz, Gabriella (Frontiers in Behavioral Neuroscience, 2020)
Previous studies suggested that both maladaptive stress response and circadian dysregulation might have a role in the background of migraine. However, effects of circadian genes on migraine have not been tested yet. In the present study we investigated the main effect of rs10462028 of CLOCK gene and its interaction with different stress factors on migraine. In our cross-sectional study 2157 subjects recruited from Manchester and Budapest completed the ID-Migraine questionnaire to detect migraine type headaches (migraineID). Additional stress factors were assessed by a shortened version of the Childhood Trauma Questionnaire, the List of Threatening Experiences questionnaire, and a validated questionnaire to identify financial difficulties. Rs10462028 showed no main genetic effect on migraineID. However, chronic stress indexed by financial difficulties showed a significant interaction effect with rs10462028 (p=0.006 in recessive model) on migraineID. This result remained significant after correction for lifetime bipolar and unipolar depression and was replicated in both subsamples, although only a trend effect was reached after Bonferroni-correction, which is the strictest correction not considering interdependences. Childhood adversity and recent negative life events showed no significant gene x stress interaction with rs10462028. In addition, in silico analysis demonstrated that the genetic region tagged by rs10462028 alters the binding of several miRNAs. Our exploratory study suggest that variations in the CLOCK gene, with moderating effect on gene function through miRNA binding, in interaction with financial difficulties might influence the risk of migraine-type headaches. Thus, financial hardship as a chronic stress factor may affect migraine through altering circadian rhythms.